Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/chd.12409
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and executive functioning in adult survivors of congenital heart disease

Abstract: Patients with severe CHD performed significantly worse on measures of processing speed, attention, and executive functioning. These findings may be useful in the long-term care of adults with congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 27 publications
3
47
0
Order By: Relevance
“…Klouda et al using a computerized battery of standardized neurocognitive tests (CNS‐Vital Signs) found that out of 48 ACHD patients, those with severe CHD had worse processing speed, attention, and executive function. Like our study, Klouda also found that the number of prior surgeries had a strong relationship to neurocognitive deficits, specifically to worse executive function …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Klouda et al using a computerized battery of standardized neurocognitive tests (CNS‐Vital Signs) found that out of 48 ACHD patients, those with severe CHD had worse processing speed, attention, and executive function. Like our study, Klouda also found that the number of prior surgeries had a strong relationship to neurocognitive deficits, specifically to worse executive function …”
Section: Discussionsupporting
confidence: 82%
“…Like our study, Klouda also found that the number of prior surgeries had a strong relationship to neurocognitive deficits, specifically to worse executive function. 11 Despite the increasing awareness of neurocognitive deficits in the ACHD population, there is little research regarding the impact of these deficits on our patients' lifestyle and quality of life. Apers et al demonstrated that educational attainment, employments status, and marital status were predictors of quality of life in ACHD patients, 12 and other prior studies have noted that ACHD patients tend to have worse educational attainment, more unemployment, and be less likely to be in a significant relationship or married.…”
Section: Discussionmentioning
confidence: 99%
“…We also tested processing speed because it has been shown to be correlated to walking performance in older adults (Chen et al, 2012; Odonkor et al, 2013) and motor adaptation in young subjects (Rodrigue et al, 2005). Cognitive switching was assessed with a Cognitive Switching Task (i.e., a set-shift task) and processing speed was evaluated with a Symbol Digit Coding Task (Figure 1B), as in previous studies characterizing age-related changes in these two cognitive functions switching (Gualtieri and Johnson, 2008; Klouda et al, 2017). In the Cognitive Switching Task, subjects had to match two objects based on randomly changing rules that were explicitly given to the subjects (i.e., “Match by color” or “Match by shape”) (Figure 1B, left panel).…”
Section: Methodsmentioning
confidence: 99%
“…However, in these cohorts, most of the adults with d -TGA had not undergone the ASO but the atrial switch procedure (operation often conducted in this population before the development of the ASO). In the study of Klouda et al (53), adults with critical CHD (i.e., d -TGA or Fontan, n  = 24, 32.8 ± 7.6 years old) had lower scores than expected in multiple domains: psychomotor speed, processing speed, sustained and executive attention, and on the overall, neurocognitive index. Tyagi et al (54) observed that d -TGA adults ( n  = 80, 19–50 years old) scored worse than those with mild CHD ( n  = 84) on an overall neuropsychological index.…”
Section: Adults With D-tga: Emerging Evidencementioning
confidence: 90%
“…Thus, to our knowledge, no studies have focused specifically on the cognitive outcomes of adults who underwent the ASO. Two recent studies (53, 54) investigated the neuropsychological outcomes of adults with CHD, including d -TGA. However, in these cohorts, most of the adults with d -TGA had not undergone the ASO but the atrial switch procedure (operation often conducted in this population before the development of the ASO).…”
Section: Adults With D-tga: Emerging Evidencementioning
confidence: 99%